PENGARUH BERBAGAI ENKAPSULAN DALAM PROSES ENKAPSULASI ASAM SITRAT SEBAGAIACIDIFIER DALAM PAKAN AYAM PEDAGING TERHADAP KECERNAAN PROTEIN DAN ENERGI MET ABOLIS - M. Halim Natsir (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2009)
The   aim   of   this   research   was   to   examine   the   influence   of   several encapsulants  in encapsulating citric  acid  used as acidifier  on protein digestibility and  metabolizable   energy   in broilers.   The  materials   used  in  this  research   were  20 broilers   of  21  days   of  age,   liquid   citric   acid  and  encapsulated   citric   acids.   The encapsulants     used   were   maltodextrin,     lactoglobulin     and   zeolite.    Broilers    were randomly   allotted   to five   dietary   treatments   with  4 replication    each.   The  variables observed     were    crude   protein    digestibility   (DCPmanure    and    DCP/aecaiJ.    apparent metabolizable   energy  (AME) and  apparent  metabolizable   energy  corrected  N  (AMEn). Data  were  analyzed   by using  Completely   Randomized   Design.   The difference   among the treatments   was further  tested  by using Duncan  Multiple   Range   Test.  The result of this  research   showed   that   while   citric  acid  encapsulated    with   maltodextrine   gave significantly    different    effect   (P<0.05)    and   the   highest   crude   protein    digestibility (DCPmanurd.   citric  acid  encapsulated   with  either  lactoglobulin   and  and  maltodextrine gave  significantly  highest   results  on  digestibility   (DCP1aecaiJ  (P<0.05)    and  AME  and AMEn   (P<0,01).     It  can   be   concluded   that   maltodextrin    was   the   best   choice   of encapsulant for  citric  acid  based  on the highest protein   digestibility   and  metabolizable energy (JIIPB  2009 Vol  19 No 1: 1-9). Key  words   :   Citric  Acid,  Encapsulation,    Protein  Digestibility,    Metabolizable    Energy, Broiler